Key Legal Issues for non Spanish Insurance Companies in Spain ( Insurance Law, Taxes and Regulatory Law) - Ruiz Rodríguez, Segundo (Cizur Menor, Navarra Aranzadi, 2013)
It is necessary to point out what this book is not. It is not a systematic and extensive study about all the legal matters concerning insurance in Spain. It is not a doctrinal essay about theoretical issues nor a simple guide to superficial matters. However, this book is a practical and an indepth study of some difficult and specific legal subjects which are key in the development of insurance business in Spain for a non Spanish insurance company, above all if it is in the EEA. How does the author know that these are the key subjects? The answer is simple: it is based on several reports that his Law Firm, LEGSE Abogados, has prepared over a period of 15 years, responding to some habitual questions asked by non Spanish insurance companies, which are clients of theirs.
Keywords: Derecho mercantil